Entrepreneurial Leadership and Technology Adoption: The Roles of Islamic Work Ethic and Theological Trust - Mona Novita; Miftah Hur Rahman Zh; Mohd Kasturi Nor Abd Aziz; Elce Purwandari; Rahmad Hidayat; Rokimin Rokimin (Journal of Educational Technology and Learning Creativity, 2026)
Purpose of the study: This study examines the determinants of artificial intelligence and learning management system adoption among lecturers and students in Islamic Educational Management programmes at Indonesian Islamic higher education institutions, with Islamic Work Ethic and Theological Trust positioned as direct predictors of behavioural intention. Methodology: A quantitative cross-sectional survey was administered to 385 respondents drawn from twelve Islamic higher education institutions across five Indonesian regions. Data were analysed using Partial Least Squares Structural Equation Modelling in SmartPLS 4.0, and a Multi-Group Analysis compared lecturers and students after a Measurement Invariance of Composite Models procedure. Main Findings: Performance Expectancy (β = 0.287), Islamic Work Ethic (β = 0.224), Social Influence (β = 0.198), and Theological Trust (β = 0.176) significantly predicted Behavioural Intention, explaining 61.3 percent of its variance. Effort Expectancy was non-significant. Behavioural Intention (β = 0.418) and Facilitating Conditions (β = 0.312) jointly predicted Use Behaviour, explaining 48.9 percent of its variance. The Multi-Group Analysis revealed stronger Performance Expectancy effects among lecturers and stronger Social Influence effects among students. Novelty/Originality of this study: PThis study provides empirical evidence that Islamic Work Ethic functions as a direct predictor rather than a moderator of technology adoption intention in Indonesian Islamic higher education, and it introduces Theological Trust as a construct that captures user concerns about the doctrinal accuracy of artificial intelligence outputs in Islamic content. These extensions are interpreted through entrepreneurial leadership as a guiding lens that links innovation, stakeholder mobilization, and risk assessment in faith-based educational institutions.